KORELASIANTARA VITALITAS PSIKIS DAN KOMPETENSIPSIKOMOTOR DENGAN KOMPETENSI KOGNITIF MATA PELAJARAN BIOLOGI SMA NEGERI 2 SRAGEN (RELATIONSHIP AMONG THE PSYCHOLOGICAL VITALITY AND PSYCOMOTOR COMPETENCE WITH THE COGNITIVE COMPETENCE ON BIOLOGY OF SMAN 2 SRAGEN) - MARLINA, ROHMI; ROSYIDI, ALVI; HARLITA, HARLITA (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2006)
This research was carried out upon the X grade student of SMA Negeri 2 Sragen. This research wereaimed to find the correlation between psychic vitality and cognitive, correlation between psychological competence and psychomotor competence with cognitive competence on biological learning and the dominant contribution for each independent variable to cognitive competence on biological learning. This is a descriptive-quantitative research with ex post facto. The population of the study is the X grade of SMA Negeri 2 Sragen in academic year of 2004/2005. The sampling technique used is Simple Random Sampling. Sample was taken on 40 students within 8 classes. The data was then analyzed by using MultipleLinear Regretions.The result of research showed that there is positive correlation between psychological vitality and cognitive competence on biological learning of the X grade students of SMA Negeri 2 Sragen (r,ty = 0.424 with Fstatistic = 8'325 ) Ftabte (1,38; 0.0, = 4.10). Positive correlation was obtqin betyveen psychomotor competence andÂ cognitive competence onbiological learning(r,zy=0.346withF,so,;,,ir=5.163 )Ftabte(1,38;0.0s)=4.10. Thereis positive correlation between psychological vitality and psychomotor competence with cognitive competence on biological learning (R = 0.5036 with F,r,;,,i, = 6.285 ) Ftabte (2,37;0.05) = 3.25). psychic vititity is the iidependent variable giving a dominant cantribution to cognitive competence on biological with contribution of O2.St Vo.